Perkembangan Sosial Emosional yang Tidak Tercapai pada Anak Usia Dini - Nur janah (STAINU Purworejo, 2018)
This research discuss social emotional development of early childhood in TK IT Plus Mutiara Bantul Yogyakarta.This research uses qualitative descriptive approach directed to a field research. The data is acquired from interview, observation, and another data collecting which is support this research. The result of this research is (1) Social emotional development which are not achieved by early childhood in TK IT Plus Mutiara Bantul Yogyakarta, they are: have not been able to cooperate with friends, the tolerance attitude that appears depends on the mood, in expressing emotions when happy or sad is overwhelming, enthusiastic only about 5 minutes, manners and courtesy cannot yet be implemented, persistent attitude and appreciate other people's excellence have not yet appeared (2) Factors causing emotional social emotional development that is not achieved include improper parenting patterns, lack of attention due to the busyness of parents, and the lack of cooperation between the school with the family